Pressure, Feed Rate, and Abrasive Mass Flow Rate Influence on Surface Roughness for Recombinant Bamboo Abrasive Water Jet Cutting - Rongrong Li; Mats Ekevad; Xiaolei Guo; Pingxiang Cao; Jie Wang; Qingqing Chen; Hong Xue (BioResources, 2015)
The effects of pressure, feed rate, and abrasive mass flow rate on surface roughness were investigated during abrasive water cutting of recombinant bamboo. Two different thicknesses (10 mm and 15 mm) of recombinant bamboo were cut in the longitudinal and transversal directions by abrasive water jet. All experiments were arranged using response surface methodology. The parameter Ra was selected to represent the surface roughness. The value of Ra increased with an increase in feed rate and abrasive mass flow rate, but decreased with an increase in pressure. The surface roughness was lower when cutting the fiber longitudinally than when cutting transversally.